Malaria and anemia in children under 7 years of age in the western region of Côte d’Ivoire - Ehouman, Mocket Adolphe; N’Goran, Kouakou Eliezer; Coulibaly, Gaoussou (Frontiers in Tropical Diseases, 2022)
Background Anemia is a major public health problem, affecting nearly one-quarter of the world’s population. It is defined as a reduction in the hemoglobin level in the peripheral blood to below the normal threshold set for a particular population. Very often in the subtropics, helminths or malaria co-infect an individual, causing morbidities that vary by age and region. This study aims to characterize the type of anemia observed in children under 7 years of age infected with malaria in the western region of Côte d’Ivoire, to recommend a better strategy of care. Methods The study was carried out from March 2020 to May 2021 in 22 villages in Man, Tonkpi Region, with a cohort of 451 children, both male and female, aged from 3 months to 6 years. The children provided venous blood samples for the diagnosis and characterization of anemia (full blood count), and Giemsa staining (GS) (thick and thin smears) and rapid diagnostic tests (RDTs) were used for the diagnosis of malaria. Risk factors and morbidity profiles were assessed using a questionnaire. Logistic regressions models were employed to identify independent risk factors and morbidity patterns associated with Plasmodium falciparum mono-infection and co-infections. Results Of the 451 children who completed the study, 221 (49.0%) were female and 230 (51.0%) were male. The prevalence of anemia was 55.0%, distributed as 30.7% mild, 66.1% moderate, and 3.2% severe anemia. The characterization of anemia revealed that hypochromic microcytic anemia (HMA) was the predominant type, being found in 195 (78.63%) children. It was followed by normochromic microcytic anemia (29 children, 11.69%), normochromic normocytic anemia (14 children, 5.65%), and, finally, hypochromic normocytic anemia (10 children, 4.03%). The prevalence of malaria was 66.7% and 78.3% based on GS and RDTs, respectively. The closed association between malaria (Plasmodium) and anemia led to P. falciparum alone causing 56.7% of mild, 51.3% of moderate, and 37.5% of severe anemia in children. Conclusion Malaria infection was highly prevalent among children aged ≤ 7 years in both sex and in different age groups, although the number of Plasmodium parasites present during infections was greatest in younger children. Similarly, the prevalence of anemia was high, with moderate anemia and HMA being more prevalent in children ≤ 7 years of age in the western region of Côte d’Ivoire.